ENVIRONMENTAL PROBLEMS OF LAND USE DURING THE PERIOD OF MARTIAL LAW - Obikhod, Tetiana (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: in the conditions of a military operation, to consider the problematic issues of ensuring demining of Ukrainian lands for planting, to find means and methods for overcoming the ecological collapse in the country. Methods: include both the legal component of the analysis of the state of land management in Ukraine, as well as empirical methods of data collection and processing for comparison and theoretical justification of the tasks. Results: the problems of the legal status of land use were updated; the environmental problems of Ukraine as a result of the military operation are outlined, the technical and administrative component of ensuring sowing operations is highlighted. Discussion: components of a comprehensive approach to the regulation of land use both in land law and in administrative law, the formation of technical methods for overcoming problems related to land demining of Ukraine. Ukraine is one of the world’s leading countries in the field of agribusiness. And the legal component of land law plays a decisive role in this. Land law in Ukraine has been one of the most critical and complex spheres of state activity for decades. Another important and complex task of land use is the demining of lands that are or were in the war zone. A sowing campaign is underway, but it is impossible to implement it in full. According to national and international organizations, including the Red Cross and the United Nations, more than 10,000 people were killed or injured by explosions of anti-tank mines and other weapons of war. Tens of thousands of hectares of land remain mined and dangerous for the life and health of the local population. The most mined areas are in the war zone in eastern Ukraine, where the conflict with pro-Russian forces continues. To speed up demining of de-occupied territories, technical reinforcement is urgently needed: mechanized demining machines, robotic systems for demining mines, special armored vehicles for transporting explosive objects, metal detectors and means of communication. Such mechanized demining machines work remotely and can be controlled at a distance of up to one and a half kilometers. Special equipment provides efficient and fast work, as it surveys and demines large areas. The environmental consequences of war are staggering. According to the data of the Ministry of Environment, Ukraine has already recorded more than 2,300 facts of environmental crimes, and the estimated amount of damages is more than 51 billion dollars. To carry out demining, sappers of the State Emergency Service need to use special machines. In general, various means of demining land are important, i.e., the use of special technologies and tools used to find and neutralize mine contamination on land. The most common devices and equipment for land demining include: metal detectors; GPR - electronic devices that scan the soil and image underground structures; magnetic sensors; drones and unmanned aerial vehicles. Administrative support is an important component of overcoming the above-mentioned consequences of a military operation, prevention of man-made disasters and effective land use. Administrative support for land demining includes: creation of appropriate rules and regulations for the management and demining of contaminated territories; management of technological processes related to the disposal of mine pollution; control over the activities of subcontractors that carry out land demining work and others.